PENGGUNAAN INTERACTIVE FLIP PANEL DISPLAY (IFPD) DAN MEDIA MINIATUR LISTRIK DALAM MENINGKATKAN HASIL BELAJAR IPAS MATERI LISTRIK KELAS V SD NEGERI 200508 PADANGSIDIMPUAN - Hasibuan, Barumun Parulian; Fujiwaty; Poltak Pembangunan Harahap; Safril Abidin Hasibuan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study is the low learning outcomes of class VA students of SD Negeri 200508 Padangsidimpuan. This study aims to determine whether the use of. This type of research is Classroom Action Research (CAR) which is carried out in three cycles and each cycle is held three meetings. Each cycle in this study goes through 4 stages, namely, the planning stage, the implementation stage, the observation stage, and the reflection stage. The subjects in this study were 22 students of class VA SD Negeri 200508 Padangsidimpuan. Data collection techniques used were observation, tests and documentation. Based on the analysis of learning outcome test data in the pre-cycle of 22 students who were the subjects of the study, there were only 5 students or 23% who reached the complete category. Meanwhile, the majority of students, namely 17 people or 77%, were still in the incomplete category. This data shows that the majority of students have not succeeded in achieving the Learning Objective Achievement Criteria (KKTP) which is 76 which has been set. In cycle I, from a total of 22 students, 15 students successfully reached the complete category, while only 7 students with a percentage of 32% were still in the incomplete category. This data shows that Cycle II still needs to be carried out with several improvements to the steps and arrangement of media layout. In this cycle II, from a total of 22 students, all completed with a percentage of 100%, so it can be concluded that learning in cycle II learning outcomes have been completed. The conclusion in this study is that through the Use of Interactive Flip Panel Display (IFPD) and Electric Miniature Media can improve the learning outcomes of Science on electricity material for Grade V students of SD Negeri 200508 Padangsidimpuan.